Contextualizing and pilot testing the Mental Health Gap Action Programme Intervention Guide (mhGAP-IG) to primary healthcare workers in Kilifi, Kenya - Bitta, MA; Kariuki, SM; Omar, A; Nasoro, L; Njeri, M; Kiambu, C; Ongeri, L; Newton, CRJC (Cambridge University Press, 2020)
Background: Little data exists about the methodology of contextualizing version two of the Mental Health Gap Action Programme Intervention Guide (mhGAP-IG) in resource-poor settings. This paper describes the contextualisation and pilot testing of the guide in Kilifi, Kenya. Methods: Contextualisation was conducted as a collaboration between the KEMRI-Wellcome Trust Research Programme (KWTRP) and Kilifi County Government's Department of Health (KCGH) between 2016 and 2018. It adapted a mixed-method design and involved a situational analysis, stakeholder engagement, local adaptation and pilot testing of the adapted guide. Qualitative data were analysed using content analysis to identify key facilitators and barriers to the implementation process. Pre- and post-training scores of the adapted guide were compared using the Wilcoxon signed-rank test. Results: Human resource for mental health in Kilifi is strained with limited infrastructure and outdated legislation. Barriers to implementation included few specialists for referral, unreliable drug supply, difficulty in translating the guide to Kiswahili language, lack of clarity of the roles of KWTRP and KCGH in the implementation process and the unwillingness of the biomedical practitioners to collaborate with traditional health practitioners to enhance referrals to hospital. In the adaptation process, stakeholders recommended the exclusion of child and adolescent mental and behavioural problems, as well as dementia modules from the final version of the guide. Pilot testing of the adapted guide showed a significant improvement in the post-training scores: 66.3% (95% CI 62.4-70.8) v. 76.6% (95% CI 71.6-79.2) (p < 0.001). Conclusion: The adapted mhGAP-IG version two can be used across coastal Kenya to train primary healthcare providers. However, successful implementation in Kilifi will require a review of new evidence on the burden of disease, improvements in the mental health system and sustained dialogue among stakeholders.